Constrained Nanoparticles Deliver siRNA and sgRNA to T Cells In Vivo without Targeting Ligands. Issue 41 (29th August 2019) - Lokugamage, Melissa P.; Sago, Cory D.; Gan, Zubao; Krupczak, Brandon R.; Dahlman, James E.
Abstract: T cells help regulate immunity, which makes them an important target for RNA therapies. While nanoparticles carrying RNA have been directed to T cells in vivo using protein‐ and aptamer‐based targeting ligands, systemic delivery to T cells without targeting ligands remains challenging. Given that T cells endocytose lipoprotein particles and enveloped viruses, two natural systems with structures that can be similar to lipid nanoparticles (LNPs), it is hypothesized that LNPs devoid of targeting ligands can deliver RNA to T cells in vivo. To test this hypothesis, the delivery of siRNA to 9 cell types in vivo by 168 nanoparticles using a novel siGFP‐based barcoding system and bioinformatics is quantified. It is found that nanomaterials containing conformationally constrained lipids form stable LNPs, herein named constrained lipid nanoparticles (cLNPs). cLNPs deliver siRNA and sgRNA to T cells at doses as low as 0.5 mg kg −1 and, unlike previously reported LNPs, do not preferentially target hepatocytes. Delivery occurs via a chemical composition‐dependent, size‐independent mechanism. These data suggest that the degree to which lipids are constrained alters nanoparticle targeting, and also suggest that natural lipid trafficking pathways can promote T cell delivery, offering an alternative to active targeting approaches. Abstract : With DNA barcoding techniques, the delivery of siRNA to 9 cell types in vivo by 168 nanoparticles is observed. It is found that novel nanomaterials, containing conformationally constrained lipids, preferentially deliver siRNA and sgRNA to spleen T cells and do not target hepatocytes. These data demonstrate that these constrained lipids can utilize natural T‐cell trafficking to promote delivery without an active ligand.